Makna Perencanaan dalam Manajemen Pendidikan Islam - Arif Shaifudin (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2021)
Islamic education is one of the institutions which has not a light responsibility in order to generate the future Rabbani generations, but they have to be able to keep and respect the same human rights as the expression of social human. The institution of Islamic education is well-known as the second place which has some prestige and guarantees for achieving the future learners. Such assumption has proven that mostly some weaknesses are being discovered in the institution of Islamic education in implementing their learning process as the provider establishment of the country in realizing the quality of these generations for their social need and theirs lives in communities. One of the main weaknesses was in management or institutional administration, especially in the planning function. It seemly that this institution conducted their (planning) management of activities from generation to generation are mostly oriented to the Islamic education contexts, in which the doctrine of religion is being considered to be normative in all aspects like the form of learners’ experiences. The research was a literature review that aims as the reference for the institution of Islamic education on what they have been considered that the good planning is an important factor in the management of Islamic education in order to achieve the learning as effectively and efficiently.